Protective Effect of Ganoderma atrum Polysaccharides against Cadmium-Induced Injury in Human Embryonic Kidney Cells - WANG Linchun, TANG Dandan, WANG Xihe, ZHANG Qinghai (Shipin Kexue, 2025)
Objective: To investigate the protective effect of Ganoderma atrum polysaccharides (GAP) on cadmium (Cd)-induced injury in human embryonic kidney cells (HEK-293). Methods: A cell injury model was established by exposure to 2 μg/mL Cd, and 100 μg/mL GAP was used for intervention. The cell viability was determined using the Cell Counting Kit-8 (CCK-8) assay. The activities of lactate dehydrogenase (LDH), catalase (CAT), and superoxide dismutase (SOD) were measured, as well as the levels of glutathione (GSH) and malondialdehyde (MDA). The levels of reactive oxygen species (ROS) and mitochondrial membrane potential were determined using a fluorescence microplate reader. The expression of antioxidant-related genes (HO-1, Keap1, and Nrf2) and mitochondrial autophagy-related genes (PINK1, Parkin, P62, and LC3) was measured by polymerase chain reaction (PCR). Results: 100 μg/mL GAP could inhibit Cd-induced cytotoxicity and significantly increase cell viability (P < 0.05); it decreased LDH, ROS, and MDA levels, and increased GSH, CAT, and SOD activities as well as mitochondrial membrane potential levels (P < 0.05). GAP up-regulated the expression of Nrf2 and HO-1 while down-regulating the expression of Keap1, PINK1, Parkin, P62, and LC3 (P < 0.05). Conclusion: GAP has a protective effect on Cd-induced injury in HEK cells by alleviating Cd-induced oxidative stress and excessive mitochondrial autophagy.